AN ELDERLY’S PERSPECTIVE ON THE IMPACT OF SPIRITUALITY TOWARDS DEATH ACCEPTANCE - Minnie Besin Mamauag (Belitung Raya Foundation, Indonesia, 2019)
Objective: This study explored the religious or spiritual beliefs and behaviors of the elderly that could somehow translate to their level of death acceptance or lack thereof.Methods: A total of four (4) elderly participants, ages 60 and above whom meet the criteria set for this study was interviewed to assess their spiritual upbringing and experiences that resulted to their death acceptance. The study involves qualitative approach using thematic analysis. The narrative testimony of the old adult participants in this study which includes cases of older adult that believes in God, older adult having shifted from one religious organization to another, and older adults’ instilled spirituality comes from religious imprint from family members during childhood describes the three important patterns in the religious or spiritual standing of the participants.Results: The themes signified that (1) older adults are inherently religious and this nature is a subsequent factor in (2) their faith in God basing on their life experiences and life’s meaning. Furthermore, this (3) belief or faith in God offers them a sense of security and hope in the afterlife.Conclusion: These themes explain the pattern in the creation of a religious/ spiritual standing that leads to death acceptance among participants as evident in their interview results.